Beyond the Thermodynamic Limit: Template for Second Law Violators - Sheehan, Daniel (Journal of Scientific Exploration, 2022)
For 150 years the second law of thermodynamics has been considered inviolable by the general scientiﬁc com-munity; however over the last three decades its absolute status has been challenged by dozens of theoretical and experimental counterexamples. This study explores commonalities between some of the most potent of these and reveals a common template that involves broken physical-thermodynamic symmetries and reser-voirs of work-exploitable thermal energy stored at system boundaries. Commercially successful second law devices could disrupt the current energy economy and help support a sustainable energy future. This article expands on a talk presented at Advanced Energy Concepts Challenging the Second Law of Thermodynamics, a symposium hosted as part of the 4th Annual Advanced Propulsion and Energy Workshop (22 January 2022). Keywords: second law of thermodynamics, Maxwell’s demon, sustainable energy